A Study and Analysis of TPMAP’s Poverty Indexes Using the Analytical Hierarchy Process - Duangrathum, Sudarat; Daengsi, Therdpong; Wongsrisa, Saharat; Rachsiriwatcharabul, Natworapol; Jumroonrut, Suttipong (Journal of Advanced Development in Engineering and Science, 2026)
This research aims to study and analyze the weighting of poverty indicators across different dimensions under the TPMAP (Thai People Map and Analytics Platform) system by applying the Analytic Hierarchy Process (AHP). The objective is to increase the accuracy of reflecting poverty issues, as the original system assigns equal weights to all five dimensions—health, education, finance, access to public services, and living conditions—which may not align with their contextual importance.The study gathered data from in-depth interviews with nine experts from various agencies involved in quality-of-life development. The data were then analyzed using AHP to transform qualitative insights into quantitative weights, while also testing the Consistency Ratio (CR) to ensure reliability. The analysis focused on the seven experts with CR values lower than 0.1, and their inputs were used to calculate new average weights.The results revealed that the education and access-to-public-services dimensions received higher weights than the others, at 27.6% and 24.4%, respectively. When the newly developed formula was applied to real data from nine northern provinces and compared with the results of the original formula, changes were observed in both the number of poor people and the provincial rankings. For example, Phayao Province moved up in ranking, demonstrating that adjusting indicator weights through AHP allows poverty issues in different areas to be more accurately reflected.This study therefore proposes the use of the Analytic Hierarchy Process as a methodological approach to improve and further develop TPMAP, enabling more effective policymaking and planning for target groups at both local and national levels.